PENGUJIAN VARIABEL MAKRO EKONOMI TERHADAP JAKARTA ISLAMIC INDEX - Farida Titik Kristanti; Nur Taufiqoh Lathifah (University of Merdeka Malang, 2013)
Stock price behavior patterns determined the pattern of return received. Stock price was not only determined bycompany profits but also influenced by economic factors, political, and financial of state. The objective of thisresearch was to examine the effect of macro economy variables, namely inflation, Interest rate, and foreignexchange to Jakarta Islamic Index in the long term and short term in 2008-2012 periods. This study usedsecondary data, while the methods of analysis used were the data stationary test (Augmented Dickey Fuller),co-integration test and error correction model. The results of this study indicated that all the variables had beenstationary. Co-integration test showed that there was a long-term relationship among the variables. There wasa long term relationship among inflation, interest rates and foreign exchange rates to the Jakarta Islamic Indexfor 2008-2009 periods, while the Error Correction Model test showed that there was a short-term relationshipamong inflation, interest rates and foreign exchange rates to the Jakarta Islamic Index for 2008-2009 periods.